If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) = 5x + 6 Reorder the terms: 3(4 + x) = 5x + 6 (4 * 3 + x * 3) = 5x + 6 (12 + 3x) = 5x + 6 Reorder the terms: 12 + 3x = 6 + 5x Solving 12 + 3x = 6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 12 + 3x + -5x = 6 + 5x + -5x Combine like terms: 3x + -5x = -2x 12 + -2x = 6 + 5x + -5x Combine like terms: 5x + -5x = 0 12 + -2x = 6 + 0 12 + -2x = 6 Add '-12' to each side of the equation. 12 + -12 + -2x = 6 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 6 + -12 -2x = 6 + -12 Combine like terms: 6 + -12 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 8x^4+10x^3+9x^2+x-1=0 | | 7x-10=3x+26 | | 10x-6 = 114 | | 1+2n-3=74 | | 15x+77=77 | | 7.19m/2 | | 4x+30+2x+15=90 | | 28=2b/5-2 | | (5x-14)=(3x+4) | | 4x=10x+5 | | 2x+15=4x+30 | | 4x+1=2(x+7) | | -11=m+1+2n | | 3z+5+7z-5=90 | | 8a-5=27 | | 12y/4-8=33 | | 2(a-2)=5(9-a) | | 50h+20= | | x^2+10x=-12 | | 6x-8=1/2(6x | | 14f+21= | | 5/7*-13=26 | | (a+16)(a-18)=180 | | 3(x-7)=24-9x | | 2(2x-1)=2(x+2) | | -4+-1= | | 5y+18=43 | | 4a-3*2=-4 | | 12w-36= | | y+18=47 | | Y-2=3x+4 | | 8.5x^3-79.6875x-164.171=0 |